The impacts of microcredit on poverty reduction evidence from Cambodian rural villages - Phim, Runsinarith (Philippine Review of Economics, 2014)
This paper attempts to assess the poverty impact of microcredit for a panel of 827 households surveyed in 2001, 2004, and 2008 using propensity score matching (psm) and the difference-in-difference (did) method. The result shows that the poverty headcount in the microfinance institution (mfi) sample, which was highest in 2001, dropped faster compared to those in two other samples. This finding suggests that using loans from mfis may have a positive effect on poverty reduction. The result of regression analysis based on the sample with the common support using the did approach confirms the same results reflecting in higher per capita consumption expenditure, higher food expenditure, higher education expenditure, and higher healthcare expenditure over 2001-2004. Over a longer term 2001-2008, however, the effect of using mfi loan is still found to be significant and positive on only per capita consumption and per capita food consumption.